Ax-[-bx-(ab ax-bx) 2ab]-(2ax-ab)
Anônimo:
Esse A, faz parte? do início?
Respostas
respondido por:
3
Acredito que sua versão seja essa (adotei sinal de "+"):
ax - [ - bx - (ab + ax - bx) + 2ab] - (2ax - ab)
= ax - [ - bx - ab - ax + bx + 2ab] - 2ax + ab
= ax - [ - ab - ax + 2ab] - 2ax + ab
= ax - [ ab - ax] - 2ax + ab
= ax - ab + ax - 2ax + ab
= 2ax - 2ax
= 0
-----------------------------------------------------------------------------------------------------
Adotei sinal de "menos":
= ax - [- bx - (ab - ax - bx) - 2ab] - (2ax - ab)
= ax - [ - bx - ab + ax + bx - 2ab] - 2ax + ab
= ax - [ - 3ab + ax] - 2ax + ab
= ax + 3ab - ax - 2ax + ab
= 4ab - 2ax
= 2a(2b - x)
ax - [ - bx - (ab + ax - bx) + 2ab] - (2ax - ab)
= ax - [ - bx - ab - ax + bx + 2ab] - 2ax + ab
= ax - [ - ab - ax + 2ab] - 2ax + ab
= ax - [ ab - ax] - 2ax + ab
= ax - ab + ax - 2ax + ab
= 2ax - 2ax
= 0
-----------------------------------------------------------------------------------------------------
Adotei sinal de "menos":
= ax - [- bx - (ab - ax - bx) - 2ab] - (2ax - ab)
= ax - [ - bx - ab + ax + bx - 2ab] - 2ax + ab
= ax - [ - 3ab + ax] - 2ax + ab
= ax + 3ab - ax - 2ax + ab
= 4ab - 2ax
= 2a(2b - x)
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás